Auditor Switching: New Evidence from Indonesia - Yenny Wati (The Indonesian Journal of Accounting Research, 2020)
The purpose of this research is to determine the direct influence of KAP size, company size, audit delay, audit tenure, previous year’s audit opinion, opinion shopping, financial distress, audit fee, company growth on auditor switching as well as through going concern audit opinion as a mediating variable. The data used in this research are secondary data involving 104 manufacturing company listed on the Indonesia Stock Exchange for the period 2013-2017. The data used in this study were analyzed using partial least square and carried out with the help of sotfware WarpPLS 5.0. The results show that KAP size, company size, audit delay, audit tenure, financial distress has a negative effect on auditor switching. Previous year’s audit opinion, opinion shopping, audit fee, company growth, going concern audit opinion has a positive effect on auditor switching. KAP size, company size, audit delay, audit tenure, previous year’s audit opinion, audit fee has a negative effect on going concern audit opinion. Opinion shopping, financial distress, company growth has a positive effect on going concern audit opinion. The result also show partial mediation of going concern audit opinion on impact KAP size, company size, audit delay, audit tenure, opinion shopping, financial distress, audit fee, company growth on auditor switching. Full mediation of going concern audit opinion on impact of previous year’s audit opinion on auditor switching. Our findings provide new empirical evidence supporting the profession's arguments that mandatory audit partner rotation is costly to multiple stakeholders, including clients, auditors, and investors.